Participation, Slack, and Budget-Based Performance Evaluation - Kirby, Alison J.; Reichelstein, Stefan; Sen, Pradyot K.; Paik, Tae-Young (Journal of Accounting Research, 1991)
Alison J. Kirby, Stefan Reichelstein, Pradyot K. Sen, Tae-Young Paik, Participation, Slack, and Budget-Based Performance Evaluation, Journal of Accounting Research, Vol. 29, No. 1 (Spring, 1991), pp. 109-128